ANALISIS ANGGARAN BIAYA SEBAGAI ALAT PENGENDALIAN MANAJEMEN PADA PT. XYZ - Cia Najiibah Najah (Ikatan Dosen Menulis, 2023)
The purpose of this research is to identify and describe the causes of the difference between the budget and the adverse realization and the handling efforts made by PT XYZ. The research method used is descriptive with a qualitative approach. The methods used in this research process come from interviews and documentation from the cost budget report data for 2021-2023 at PT XYZ. The data analysis technique uses Miles and Huberman. The findings of this study indicate that there are 2 factors that cause the difference in budget losses at PT. XYZ, internal factors, namely the company management has not been optimal in analyzing the development of budget realization and lack of coordination between members. While external factors are delays in material delivery so that the project is completed late. The control efforts made are to carry out good budget planning, analyze the cost budget, add several suppliers, and conduct a price survey first.